Between welcome space and welcome culture: A systemic study - Mamprin, Caterina; Papazian-Zohrabian, Garine (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2023)
Over the past decade in Quebec, enrollment has risen noticeably in “reception classes,” a program oriented toward teaching the French language. In this article, we study the experience of a department of second-language teachers from a systemic perspective. Eight high school teachers from the Greater Montreal area participated in this qualitative multiple-case study. Using a systemic model, we studied how the recent opening of new reception classes, the relationships between teachers from in and outside the classes, and the misunderstanding of the program by school staff created a gap between the reception department and the regular programs. Our results shed light on the importance of promoting a welcoming culture within the school.